Tinjauan Hukum Islam terhadap Praktik Jual Beli Ikan antara Nelaya dengan Bakul (Tengkulak) di Pelabuhan Perikanan Bulu-Tuban. - Murtadlo, Fakhri Ali; Fahrullah, (Universitas Negeri Surabaya, 2019)
Buying and selling is an economic activity that involves several parties who are trying to make a profit in order to make ends meet. Buying and selling between fishermen and middleman in the Bulu-Tuban fishing port contains an element of cooperation. This study uses a descriptive qualitative method with the aim to find out an Islamic legal review of the fish buying and selling mechanism between fishermen and baskets at Bulu-Tuban Fishing Port.Based on the results of the study found the practice of tadlis, gharar and talaqqi ruqban in the mechanism of fish trading between fishermen and baskets. The sale and purchase of fish between fishermen and baskets in the Bulu-Tuban Fishery Port is not right according Islamic law that refers to Al-Qur'an surah An-Nisa verse 29 because in the sale and purchase it has not yet achieved justice and there are still practices that are not allowed in Islamic rules.